DEPRESSION, ANXIETY AND USE OF MEDICINES IN PSYCHOLOGY ACADEMICS - Soares, Wellington Danilo (2021)
Anxiety and depression are emotional disorders that can be caused by stressful factors in the academic as well as in the professional sphere. The objective was evaluating the prevalence of depression, anxiety and medication use in psychology students. This is a quantitative, cross-sectional and comparative research. The students of the Psychology of a private institution of higher education in the city of Montes Claros – MG, were the target audience. Thirty-three night-time students of both genders, aged 18 or older, were randomly selected. Three questionnaires were used, Beck Depression Inventory, Anxiety Beck Inventory and Morisky-Green Test that aimed to contribute to the identification of issues related to anxiety and depression and medication use. The results showed a higher prevalence of female students (81.8%). Through the data it was possible to reveal that by joining the moderate and severe anxieties we have almost one third of the group surveyed (30.4%). As for depression, it was evidenced that (54.5%) they do not present a depressive condition, and that the researched public is less adherent to the use of medications (72.7%). The results found allow us to conclude that there is a higher prevalence of anxiety symptoms among students and, consequently, the use of medications, so as not to leave it aside even at times when it is feeling well, and a lower prevalence referring to symptoms of depression.